Kasus Vina Cirebon, Media Sosial Sebagai Sarana Mencari Keadilan - Faisyal, Faisyal; Sukmaranti, Galuh (FISIP Universitas Bung Karno, 2024)
No viral no justice agadium is sweeping the law in Indonesia. The murder case of Vina Ciberon was legally reviewed, because the case went viral on social media. There is a movement from the community called netizens or netizens to fight the law through social media. They collected data on the internet and made an investigation report, then shared it with the public through their respective social media. Some have even become citizen journalists, conducting investigations, and compiled into news and disseminated through social media. The data obtained is quite accurate, and can be a source of law. Social movement theory explains that social movements outside the context of established institutions can be successful if carried out collectively. Netizens as a group are able to use social media as a means of social and legal resistance. This happened in the case of Vina's murder.Keywords: Social media, citizen journalism, social media-based social movements.